Development of a High Heat Flux Electric Joule Heating System for Testing a One-Side Heated Cooling Channel. (3rd April 2022) - Hwang, Donkoan; Park, Minkyu; Oh, Hoongyo; Lim, Ji Hwan; Kim, Moo Hwan; Chai, Kil-Byoung; Jo, HangJin
Abstract: Systems such as solar thermal systems, chip coolers, beam dumps of neutral beam injectors, and fusion reactor divertors and blankets are subjected to one-side high heat flux. Specifically, high heat flux (10 MW/m 2 ) is applied on the fusion reactor divertor in steady state. The monoblock design in a divertor is limited by the thermal-hydraulic and mechanical stability, which thermal-hydraulic data are required for. The lack of thermal-hydraulic data for the cooling channel causes difficulties for the design of the monoblock and the determination of the thermal-hydraulic condition for the safety and conversion of energy efficiency. To analyze the mechanisms and thermal hydraulics, a high heat flux heating system is recommended for the purpose of testing one-side heated cooling channels. Comparing an e-beam system to a joule heating system, the e-beam system requires higher cost, expertise, sophisticated design, and more power consumption, which delays the development of heat transfer correlations and the mechanisms of fluid motion inside the cooling channel. The production of 10 MW/m 2 heat flux using the joule heating method is challenging, since it is limited by the temperature of the heater. In this study, the limitation of the joule heating system was overcome by optimizing the material selection for the heater, the configuration of the system, and the bonding method of the components used in the system. High heat flux testing was conducted and the target heat flux of 10 MW/m 2 was successfully implemented, and it showed good reproducibility of the heating system. The reliability of the newly developed heating system was validated by comparing the results of the experiments with correlation-based simulations. The comparison analysis showed that the experimental results from the new heating system are comparable to the single-phase and two-phase correlation-based simulation results within 5% and 1.5% error, respectively. Further, through the comparison of various correlation-based simulations with the experimental results, we conclude that one-side joule heating results are only describable using a one-side correlation, not using correlations developed from uniform heating systems. To optimize the design of the cooling channel in a one-side heating condition in a faster and easier manner, the newly advanced joule heating system will help contribute to the development of the thermal-hydraulic analysis of the cooling channel.